"Don't take your medicine lying down!". Issue 19 (23rd September 1985) - Unknown
Abstract : Tablets and capsules are commonly swallowed with little or no water 1 and many patients in bed swallow them lying down. The amount of water taken and the patient's posture can greatly influence the passage of solid medicines through the oesophagus.